Makna Pelaksanaan Ritual Puja Bakti Keagamaan Buddha Anak Usia Dini Taman Kanak-kanak Sekolah Bina Harum Bangsa - Tri Nindi Lestari (Jurnal Pelita Dharma, 2022)
The problem raised in this study is that there is no comprehensive description of the meaning of carrying out Buddhist religious rituals for early childhood in the Kindergarten of Bina Harum Bangsa School. The purpose of this study was to describe the meaning of carrying out Buddhist religious rituals for early childhood in the Kindergarten of Bina Harum Bangsa School. This research uses descriptive qualitative method. The subjects of this study were early childhood children at Bina Harum Bangsa School, early childhood teachers at Bina Harum Bangsa School, and guardians of early childhood students at Bina Harum Bangsa School. This research was carried out in January, February, and June 2021. The data collection techniques used were observation, interviews, and documentation. Test the validity of the data include credibility, transferability, dependability, and confirmamability. The data that has been obtained were analyzed using the Miles and Huberman model, namely data collection, data condensation, display, and drawing conclusions. The results of this study are: (1) the meaning of implementation is aspects of early childhood development and rituals as supporting aspects of early childhood development; (2) implementation objectives include: (a) school objectives are efforts to achieve the school's vision, mission and goals, and as an effort to implement the curriculum; (b) the aim of the teacher is to strengthen the beliefs of early childhood, to instill the value of respect for those who deserve to be respected, to practice the Buddhist way of worship, to inculcate the teachings of Buddhism, and to support aspects of the moral and religious development of early childhood; (c) the objectives of the guardians are efforts to change the bad character of children, efforts to support early childhood development, and efforts to increase the belief in Buddhist teachings for early childhood; (3) the benefits of implementation include: (a) the benefits received by the school are that the school gains the trust of parents and the community; (b) the benefits received by students are the habit of giving greetings, awareness of giving, practicing meditation, memorizing namakarapatta, practicing Buddhist Pancasila, being diligent in Buddhist Sunday School, being able to get along, being able to behave positively, being able to be tolerant, and being able to respect older people.